A model predictive control for the T-Type qZS inverter with capacitor imbalance compensation - Monteiro, Joaquim (2019)
The quasi-Z-source (qZS) inverter has emerged as one interesting solution for several types of applications, like those associated with renewable energies. The qZS inverter presents a wide range voltage gain and does not require dead times improving the system reliability. One of the most interesting qZS inverter topologies is the T-Type multilevel converter. Nevertheless, the T-Type multilevel may have issues related with the capacitor voltages imbalance. Therefore, this work proposes the use of model predictive controllers (MPC) to mitigate the capacitor voltages imbalance issue. The optimization cost functional will weight three criteria, the capacitor voltage imbalance, the level of the voltage of the series connected capacitors and the AC currents errors. To test the proposed control strategy, several simulations studies are presented and discussed.